Visualization of the flow behind a backward-facing step using a schlieren technique and tetrafluoroethane - Pititat Itsariyapinyo (Physics of Fluids, 2022)
This paper explores the possibility of visualizing the low-speed, near-wall flow using a schlieren imaging technique. In this investigation, wind tunnel testing is conducted on a backward-facing step at step Reynolds numbers of 2940, 5140, and 6120. Tetrafluoroethane is injected through a rectangular slot mounted flush to the wind tunnel floor and is introduced to the downstream region of the step as refractive tracers. The visualization acquired at the midsection suggests that the mass flux of tetrafluoroethane should be approximately 5%–10% lower than that of the freestream air to ensure that the injection is less intrusive to the flow field while still achieving the visibility required to characterize the flow field. For long-exposure photography, the reattachment length or the length scale behind the step can be estimated when the exposure time of a camera is 3.2–12 times longer than the timescale of vortex roll-up. For high-speed photography, the sequence of vortex shedding can be adequately visualized when the frame rate of a camera is at least four times higher than the vortex shedding frequency.
Keywords: Fluid Dynamics and Turbulent Flows; Aerodynamics and Acoustics in Jet Flows; Fluid Dynamics and Vibration Analysis